1999
DOI: 10.1115/1.555382
|View full text |Cite
|
Sign up to set email alerts
|

The Decomposition Mechanisms and Thermal Stability of ZDOL Lubricant on Hydrogenated Carbon Overcoats

Abstract: Tribo-chemical studies of the head/disk interface (HDI) were conducted using hydrogenated CHx carbon disk samples coated with perfluoropolyether ZDOL lubricant. The studies involved drag tests with uncoated and carbon-coated Al2O3-TiC sliders and thermal desorption experiments in an ultra-high vacuum (UHV) tribochamber. The friction and catalytic decomposition mechanisms as well as the thermal behavior of ZDOL are described, and data demonstrating the chemical reactions of the lubricant and carbon overcoat are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Chen et al [12] demonstrated that the catalytic degradation process of Zdol in the presence of Lewis acid occurs most readily at the acetal units (O-CF 2 -O) within the internal backbones (CF 2 O and CF 2 CF 2 O) instead of the end group functionals. During the sliding at the carboncoated slider/Zdol lubricated CH disk interface, frictional heating is the primary decomposition mechanism of Zdol [13]. Wei et al [14] studied the decomposition mechanisms of a PFPE Zdol at the head/disk interface under sliding conditions using an ultrahigh vacuum tribometer equipped with a mass spectrometer.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [12] demonstrated that the catalytic degradation process of Zdol in the presence of Lewis acid occurs most readily at the acetal units (O-CF 2 -O) within the internal backbones (CF 2 O and CF 2 CF 2 O) instead of the end group functionals. During the sliding at the carboncoated slider/Zdol lubricated CH disk interface, frictional heating is the primary decomposition mechanism of Zdol [13]. Wei et al [14] studied the decomposition mechanisms of a PFPE Zdol at the head/disk interface under sliding conditions using an ultrahigh vacuum tribometer equipped with a mass spectrometer.…”
Section: Introductionmentioning
confidence: 99%
“…The oxide radical will rapidly unzip the residual chain, producing CF O. Although this unzipping process has been claimed to be less likely [12], the CF O fragment was in fact detected by mass spectroscopy in a separate study [13]. The fluorocarbon radical can also degrade intact PFPE molecules by removal of a fluorine atom, thus generating a new radical [14].…”
Section: E Free Radical Degradation Mechanismmentioning
confidence: 96%
“…We must note that the effect of the difference in the thermal expansion coefficients of the DLC film and the Si substrate on the destruction will be small in comparison to that of the chemical reaction. Chen et al described in their paper that the observed decomposition temperature for a 2000 MW PFPE is 429 K with a 0.2 K/s heating rate 17) . The 4000 MW PFPE without fractional treatment is used in this study, therefore, the used PFPE molecules will have a wide MW range due to the normal distribution.…”
Section: Discussionmentioning
confidence: 99%